PERAN MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA PROMOSI MAKANAN PENUTUP MANIS KEKINIAN DI SOLO RAYA: The Role of Social Media Instagram as a Promotional Medium for Modern Sweet Desserts in Solo Raya - Supriyati, Rina Ashar; Budi Istiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the role of social media Instagram as a promotional tool in the trendy dessert industry in Solo Raya. Utilizing a qualitative research approach, this study involved five informants who are business actors in the dessert sector. The results indicate that Instagram serves as a primary platform that facilitates interaction between business actors and consumers while expanding audience reach. Several key factors identified include hobbies as the main motivation, consistency in content posting, relevance to current trends, and maintaining good relationships with Loyal Consumers. Additionally, the ease of access and interactive features of Instagram , such as stories and reels, contribute to the effectiveness of promotions. Therefore, this study concludes that Instagram functions not only as a promotional medium but also as a tool for building community and maintaining customer loyalty in the trendy dessert business in Solo Raya.